Numerical analysis of latent heat thermal energy storage using miniature heat pipes: A potential thermal enhancement for CSP plant development. (5th September 2016) - Khalifa, Abdulmajed; Tan, Lippong; Mahony, David; Date, Abhijit; Akbarzadeh, Aliakbar
Highlights: Benefits of using miniature heat pipes in latent heat storage unit were investigated. The proposed technique improved the heat spreading performance within LHTES. The effective thermal conductivity increased 320 folds with 20% volume fraction. 10% volume fraction of MHPs reduced 77% of the required HTF tube length in CSP plant. Abstract: This paper presents a study, numerically and experimentally, on a new thermal enhancement method for improving the heat transfer performance of latent heat energy storage (LHTES) using miniature heat pipes (MHPs). As commonly known, heat pipes are passive heat transfer devices which are capable in transferring large amount of heat with a small temperature drop. The heat pipe used in this study is copper-water charged MHP and has physical dimensions of 2 mm diameter and 100 mm long. The phase change material (PCM) used in the LHTES is paraffin wax (RT60) which is an organic based PCM and has a melting point of 60 °C. The attractive thermal features of using PCM as thermal mass are high heat capacity, exhibit constant temperature during phase change and poor thermal response. However, the poor thermal conductivity (∼0.2 W/m·K) of the PCM has greatly limited its potential to be used as high heat storing materials for future thermal storage developments. One of the potential developments is the concentrated solar power (CSP) plant, where LHTES can play an important role for improving the power generating efficiency. Providing simple and yet effective thermal enhancement method is favourable for LHTES to be widely applicable. In this study, MHPs are randomly mixed in the PCM to provide better heat spreading and improve the effective thermal conductivity of the LHTES. The numerical method adopted is three-dimensional heat conduction and the numerical results are validated against experimental data. The results have shown that the effective thermal conductivity of MHP-PCM composition has improved exponentially with the increasing number of MHPs used.